Hypertrophy of Adipose Tissues in Quail Embryos by in ovo Injection of All-Trans Retinoic Acid - Kim, Dong-Hwan; Lee, Joonbum; Kim, Sanggu; Lillehoj, Hyun S.; Lee, Kichoon (Frontiers in Physiology, 2021)
Excessive adipose accretion causes health issues in humans and decreases feed efficiency in poultry. Although vitamin A has been known to be involved in adipogenesis, effects of all-trans retinoic acid (atRA), as a metabolite of vitamin A, on embryonic adipose development have not been studied yet. Avian embryos are developing in confined egg environments which can be directly modified to study effects of nutrients on embryonic adipogenesis. Using quail embryos, different concentrations of atRA (0 M to 10 uM) were injected in ovo at embryonic day (E) 9 and adipose tissues were sampled at E14. Percentages of fat pad weights in embryo weights were significantly increased in the group injected with 300 nM of atRA. Also, among three injection time points, E5, 7 or 9, the E7 showed the most significant increase in weight and percentage of inguinal fat at E14. Injection of atRA at E7 increased fat cell size in E14 embryos with up-regulation of pro-adipogenic marker genes (Pparg and Fabp4) and down-regulation of a preadipocyte marker gene (Dlk1) in adipose tissues. These data demonstrate that atRA promotes hypertrophic fat accretion in quail embryos, implying important roles of atRA in embryonic development of adipose tissues.